A Tunable Glycosaminoglycan-Peptide Nanoparticle Platform for the Protection of Therapeutic Peptides - Harkanwalpreet Sodhi; Alyssa Panitch (MDPI AG, 2024)
The popularity of Glycosaminoglycans (GAGs) in drug delivery systems has grown as their innate ability to sequester and release charged molecules makes them adept in the controlled release of therapeutics. However, peptide therapeutics have been relegated to synthetic, polymeric systems, despite their high specificity and efficacy as therapeutics because they are rapidly degraded in vivo when not encapsulated. We present a GAG-based nanoparticle system for the easy encapsulation of cationic peptides, which offers control over particle diameter, peptide release behavior, and swelling behavior, as well as protection from proteolytic degradation, using a singular, organic polymer and no covalent linkages. These nanoparticles can encapsulate cargo with a particle diameter range spanning 130-220 nm and can be tuned to release cargo over a pH range of 4.5 to neutral through the modulation of the degree of sulfation and the molecular weight of the GAG. This particle system also confers better in vitro performance than the unencapsulated peptide via protection from enzymatic degradation. This method provides a facile way to protect therapeutic peptides via the inclusion of the presented binding sequence and can likely be expanded to larger, more diverse cargo as well, abrogating the complexity of previously demonstrated systems while offering broader tunability.